Woman monks: an anomaly or a misnomer? - Marja-Leena Heikkila-Horn (Universiti Kebangsaan Malaysia, 2003)
The third millennium started with a bang in Thai Buddhist circles when a former philosophy professor was ordained a Buddhist nun in Sri Lanka. The Thai Buddhist hierarchy does not recognize nuns, and has, in fact, forbidden monks to ordain women. Thailand accommodates some 300,000 Buddhist monks – and some 10,000 white-clad Buddhist women, called "mae chis". The social and spiritual status of these women has traditionally been extremely low and they are regarded as laywomen. In the English literature, they are confusingly called "nuns", hence the reluctance to use the same category for these newly ordained women. The traditional Sanskrit/Pali terms for ordained women are "bhiksuni" and "bhikkhuni", which are not well-known in Thailand, as these persons have usually been visiting Chinese, Taiwanese, Korean or Tibetan "bhiksunis". There is simply no category of genuine "nuns" in Thai society. Several women have been ordained novice nuns in either Sri Lankaor Thailand by Sri Lankan nuns after the trail-blazing act of the first Thai woman. This article argues that if this trend of ordaining women is allowed to continue, the Thai Buddhist "woman monks" will have to create a completely new category, identity and space for themselves as genuine "nuns" or bhikkhunis.